Developing a primary care patient measure of safety (PC PMOS): a modified Delphi process and face validity testing. Issue 4 (3rd July 2015) - Hernan, Andrea L; Giles, Sally J; O'Hara, Jane K; Fuller, Jeffrey; Johnson, Julie K; Dunbar, James A
Abstract : Background: Patients are a valuable source of information about ways to prevent harm in primary care and are in a unique position to provide feedback about the factors that contribute to safety incidents. Unlike in the hospital setting, there are currently no tools that allow the systematic capture of this information from patients. The aim of this study was to develop a quantitative primary care patient measure of safety (PC PMOS). Methods: A two-stage approach was undertaken to develop questionnaire domains and items. Stage 1 involved a modified Delphi process. An expert panel reached consensus on domains and items based on three sources of information (validated hospital PMOS, previous research conducted by our study team and literature on threats to patient safety). Stage 2 involved testing the face validity of the questionnaire developed during stage 1 with patients and primary care staff using the 'think aloud' method. Following this process, the questionnaire was revised accordingly. Results: The PC PMOS was received positively by both patients and staff during face validity testing. Barriers to completion included the length, relevance and clarity of questions. The final PC PMOS consisted of 50 items across 15 domains. The contributory factors to safety incidents centred on communication, access to care, patient-related factors, organisation and care planning, task performance and information flow. Discussion: This is the first tool specifically designed for primary care settings, which allows patients to provide feedback about factors contributing to potential safety incidents. The PC PMOS provides a way for primary care organisations to learn about safety from the patient perspective and make service improvements with the aim of reducing harm in this setting. Future research will explore the reliability and construct validity of the PC PMOS.